PERGOLAKAN ANTARA LIFE STYLE DAN SYARI’AT-BUDAYA DALAM KEHIDUPAN PEREMPUAN ACEH MASA KINI - Wahid, Abdul (MUWAZAH, 2013)
Abstract : Acehnese women life in the demands of the implementation of Islamic law and Aceh cultural context.  The development of today's lifestyle demands the women in Aceh to maintain these two patterns.  There are a lot of  women in Aceh have a strong commitment to keep the pattern of their life as an "Islamic Acehnese Women", because they believe that the ideal pattern of life  among  Acehnese women  do not leave their roots in the ideal values  of Islam and the cultural context.  But in many cases, the understanding of the patterns of live and cultural context of Aceh has been incorrectly interpreted and regarded as part of the teachings of Islam. Abstrak : Hidup perempuan Aceh dalam tuntutan implementasi hukum Islam dan konteks budaya Aceh. Perkembangan gaya hidup masa kini menuntut perempuan di Aceh untuk mempertahankan dua pola tersebut. Ada banyak perempuan di Aceh memiliki komitmen yang kuat untuk menjaga pola hidup mereka sebagai "Perempuan Aceh yang islami", karena mereka percaya bahwa pola hidup ideal di kalangan perempuan Aceh tidak meninggalkan akar mereka dalam nilai-nilai ideal Islam dan konteks budaya. Namun dalam banyak kasus, pemahaman tentang pola konteks hidup dan budaya Aceh telah salah ditafsirkan dan dianggap sebagai bagian dari ajaran Islam.